Multiple signaling pathways converge on proapoptotic protein BAD to promote survival of melanocytes - Konduru Seetharama Sastry (14779171) (2020)
Melanocyte survival is mediated by diverse signaling pathways. However, the molecular mechanisms they use and molecules that they target are incompletely understood. Here, we show that melanocyte survival is mediated by diverse, nonredundant signaling pathways, including ERK1/2, AKT, PKA, and PKC. Each of these pathways is exerting prosurvival effects by phosphorylating the BAD. While Ser112-BAD phosphorylation is regulated by pERK, pPKA and pPKC, Ser136 and Ser155 phosphorylation are exclusively controlled by pAKT and pPKA, respectively. Inhibition of these pathways individually resulted in only modest apoptosis; however, most significant apoptosis, as a result of BAD dephosphorylation, was seen when all pathways were inhibited concurrently. BAD phosphorylation was essential for survival of melanocytes as cells expressing phosphorylation-deficient BAD were not rescued by any of the identified pathway. Furthermore, melanocytes became insensitive to kinase inhibitor-induced apoptosis when BAD expression was knocked down by BAD-shRNA. Overexpression of BAD in melanocytes stimulated faster apoptosis in response to kinase inhibitors. Taken together, our results show that BAD is acting as a convergence point for diverse survival pathways in melanocytes. Understanding the molecular mechanisms of melanocyte survival provides fundamental new insights into physiological mechanisms involved in the development of various melanocyte pathologies such as melanoma and vitiligo. Other Information Published in: The FASEB Journal License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.1096/fj.202001260rr